Notes on Early Land Plants Today. 13. New names and synonyms in Diplophyllum (Scapaniaceae, Marchantiophyta) - Váňa, Jiří; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2013)
Schuster (1974, 2002) classified the genus Diplophyllum Dumortier (1835: 15) into four subgenera, subgen. Diplophyllum, subgen. Macrodiplophyllum Buch (1928: 29), subgen. Austrodiplophyllum Schuster (1968: 18) and subgen. Protodiplophyllum Schuster (1974: 192). Subgenus Macrodiplophyllum was shown by Vilnet et al. (2011) and Hentschel et al. (2012) to be heterogeneous. Of the three species assigned to it, two species nest with Douinia Buch (1928: 13) and the other is basal to Scapania (Dumortier 1831: 38) Dumortier (1835: 14). Of the three remaining subgenera, subgen. Austrodiplophyllum seems to differ most from the rest while subgen. Diplophyllum and subgen. Protodiplophyllum do not differ in the same degree. The main differences between the latter are in the stem cortex (sharply defined vs. ill defined) and the conspicuous vitta vs. not conspicuous. We therefore think subgen. Protodiplophyllum is better treated as a section under subgenus Diplophyllum.